Homogenitoriality between aspiration and law – remarks on Judgement n. 230/2020 of the Italian Constitutional Court - Aquironi, Ilaria (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
A recent judgement of the Italian Constitutional Court serves as a basis to rethink on the evolution of the Italian jurisprudence concerning homogenitoriality, as well as to highlight the unsatisfactory results achieved, absent any omni comprehensive legislation on the issue. The judicial decisions adopted are such that the degree of protection accorded by the Italian legal system to the child born through the use of assisted reproductive technology depends on rather secondary factors compared to the primary goal of ensuring the best interests of the child. In this sense, Judgement no. 230 of 2020 of the Italian Constitutional Court is no different: critical remarks can be raised due to the cautious approach adopted by the Court; the vulnus to the protection of the best interests of the child, linked to the dependence of the degree of protection accorded to the child on the place of his or her birth, and on the assisted reproductive technique used; the variable extent of the public policy exception; and the still prevailing use of the “adoption in particular cases” as a (unsatisfactory) means to establish a legal relationship between the intended parent and the child.
Keywords: heterologous fertilization, Italian Constitutional Court, homogenitoriality, status re- cognition, issuance of the birth certificate, legal parent-child relation, surrogate motherhood, adoption in particular cases.; heterologous fertilization; Italian Constitutional Court; homogenitoriality; status re- cognition; issuance of the birth certificate; legal parent-child relation; surrogate motherhood; adoption